Natural minds - Polger, Thomas W. (MIT Press, 2004)
In Natural Minds Thomas Polger advocates, and defends, the philosophical theory that mind equals brain--that sensations are brain processes--and in doing so brings the mind-brain identity theory back into the philosophical debate about consciousness. The version of identity theory that Polger advocates holds that conscious processes, events, states, or properties are type- identical to biological processes, events, states, or properties--a "tough-minded" account that maintains that minds are necessarily identical to brains, a position held by few current identity theorists. Polger's approach to what William James called the "great blooming buzzing confusion" of consciousness begins with the idea that we need to know more about brains in order to understand consciousness fully, but recognizes that biology alone cannot provide the entire explanation. Natural Minds takes on issues from philosophy of mind, philosophy of science, and metaphysics, moving freely among them in its discussion. Polger begins by answering two major objections to identity theory--Hilary Putnam's argument from multiple realizability (which discounts identity theory because creatures with brains unlike ours could also have mental states) and Saul Kripke's modal argument against mind-brain identity (based on the apparent contingency of the identity statement). He then offers a detailed account of functionalism and functional realization, which offer the most serious obstacle to consideration of identity theory. Polger argues that identity theory can itself satisfy the kind of explanatory demands that are often believed to favor functionalism